The Role of Adolescent Pasraman to Reinforce the Concept of Tri Hita Karana for Sekaa Truna in Bali - I Made Astra Winaya; I Gede Sujana; Gede Sutrisna; I Nengah Sudiarta (International Proceeding On Religion, Culture, Law, Education, And Hindu Studies, 2022)
This research was conducted with the consideration of the authors’ interest to examine the activities of Hindu religious educational institution (Pasraman) for adolescent as the program of customary villages in Bali to reinforce the concept of Tri Hita Karana on the youth organizational activities called Sekaa Truna. This research aims at (1) describing kinds of activities held at adolescent pasraman; (2) elaborating the existence of adolescent pasraman activities held at customary villages; (3) describing forms of Tri Hita Karana concepts implemented by Sekaa Truna in the adolescent pasraman activities. This research is a descriptive research, on which the data were collected through library research. The results of this research could be revealed as follows. First, the activities of adolescent pasraman are carried out through four models of approach, namely: Dharma Wacana, Dharma Tula, Dharma Gita, dan Dharma Kria. Second, there are three factors affecting the elaboration on the existence of adolescent pasraman activities held at customary villages in developing the concepts of Tri Hita Karana for the youth including (1)The Relevance of program objectives, (2) Stakeholder support, and (3) Program funding. Third, the form of the Tri Hita Karana concept in adolescent pasraman activities towards Parhyangan is implemented through joint prayer activities by the sekaa truna; then on the Pawongan is implemented by mutual help and cooperation in carrying out the programs of the Sekaa Truna organization; while on the Palemahan is implemented through nature conservation. Through these adolescent pasraman activities, the concept of the Tri Hita Karana is developed to the sekaa truna in order to build young generation who is capable of establishing a harmonious relationship with God, human beings, and natural surroundings.